2020
DOI: 10.1002/pros.24020
|View full text |Cite
|
Sign up to set email alerts
|

Urethral luminal epithelia are castration‐insensitive cells of the proximal prostate

Abstract: Background: Castration-insensitive epithelial progenitors capable of regenerating the prostate have been proposed to be concentrated in the proximal region based on facultative assays. Functional characterization of prostate epithelial populations isolated with individual cell surface markers has failed to provide a consensus on the anatomical and transcriptional identity of proximal prostate progenitors.Methods: Here, we use single-cell RNA sequencing to obtain a complete transcriptomic profile of all epithel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
147
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(165 citation statements)
references
References 48 publications
16
147
0
2
Order By: Relevance
“…Antigens associated with the luminal epithelial cells including KRT8 , AR , HOXB13 , KLK3 , and ACPP are expressed at similar levels between the TACSTD2 high and TACSTD2 low luminal cells. In contrast, TACSTD2 high luminal cells express a higher level of PSCA , SOX2 , and KRT7 , which is consistent with the observations from the recent single-cell analyses ( 27 , 29 ).…”
Section: Resultssupporting
confidence: 91%
“…Antigens associated with the luminal epithelial cells including KRT8 , AR , HOXB13 , KLK3 , and ACPP are expressed at similar levels between the TACSTD2 high and TACSTD2 low luminal cells. In contrast, TACSTD2 high luminal cells express a higher level of PSCA , SOX2 , and KRT7 , which is consistent with the observations from the recent single-cell analyses ( 27 , 29 ).…”
Section: Resultssupporting
confidence: 91%
“…In particular, our adult scRNA-seq dataset highlighted an extensive degree of cellular heterogeneity, in particular within the luminal epithelia. Several studies recently made similar observations either focusing on the AP ( Karthaus et al, 2020 ), the intact prostate ( Crowley et al, 2020 ; Joseph et al, 2020 ), or both the intact and castrated prostates ( Guo et al, 2020 ). Integration of these multiple datasets will provide a more global view of the transcriptional landscape of the prostate epithelium.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, single-cell transcriptomics performed in the murine AP lobe also revealed a distinct but rare luminal subpopulation anatomically lining the proximal duct and expressing Tacstd2 (Trop2), Psca as well as Ly6a (Sca-1), Krt4 and Cldn10 44 . An independent study suggested that the luminal subpopulation expressing high levels of progenitor markers such as Tacstd2 (Trop2), Psca, Ly6a (Sca-1) and Krt4 corresponds to urethral luminal cells extending into the proximal ducts of the prostate 45 . Since the luminal progenitor population identified in the VP lobe expressed all the aforementioned markers (Supplementary Figure S4A, F), we cannot rule out the possibility that they might be of urethral origin.…”
Section: Discussionmentioning
confidence: 99%